Design of a Dividing‐Wall Column Considering its Multiple Steady State Characteristic. Issue 3 (13th December 2017) - Song, Erwei; Wang, Erqiang
Abstract: A dividing‐wall column (DWC) may have more than one solution of liquid and vapor split ratio for the same feed and product streams under a fixed number of stages and reflux ratio, so the multiple steady states (MSS) of a DWC in the design stage should be considered. An improved design method of a DWC is proposed by studying its MSS characteristics. Additional steps are inserted after optimization to check if MSS exist for the obtained optimal solution of vapor and liquid split ratio, and further to select the best candidate. Finally, two cases of three‐product DWCs are described to verify this method. The results indicate that multiple solutions exist for these cases, which confirm the necessity of this method and provide an important guidance for the flowing design of a DWC. Abstract : To reduce the high energy costs in distillation, the thermally coupled distillation column is a good alternative. Compared with the traditional distillation column, the dividing‐wall column has more degrees of freedom in design and optimization, which may lead to multiple steady states. An improved design method of such column based on its multiple steady states characteristics is proposed.